SPRAY DRIED LACTOSE BASED PRONIOSOMES AS STABLE PROVESICULAR DRUG DELIVERY CARRIERS: SCREENING, FORMULATION, AND PHYSICOCHEMICAL CHARACTERIZATION - Nasr, Ali; Qushawy, Mona; Swidan, Shady (International Journal of Applied Pharmaceutics, 2018)
Objective: In the present investigation efforts were considered to optimize the different conditions for the preparation of spray dried lactose based proniosomes. The aim of this research was to investigate the feasibility of proniosomes as stable precursors for the development of niosomes as oral drug delivery system for poorly water-soluble drugs. Methods: A total of twenty-eight plain proniosomal formulae were prepared with various surfactant-cholesterol loading ratios in each formula using spray dried lactose as a carrier. Span 20, 40, 60 and 80 were used in various molar ratios with cholesterol. Different evaluation techniques were performed to study the performance of the prepared proniosomes. The micromeritic properties of the prepared proniosomes were analyzed. The reconstituted niosomes were further evaluated for morphological characterization using transmission electron microscope (TEM), particle size analysis, zeta potential, and polydispersity index (PDI). Finally, selected proniosomal formulae were tested for stability study. Results: The proniosomal formulae prepared using span 40 and span 60 exhibited excellent flowability while those prepared with span 20 and span 80 showed poor flow properties. TEM photographs revealed that the vesicles were discrete, spherical without aggregation. The mean vesicle size of reconstituted niosomes was found to be in the range between (252.9±0.43–624.3±0.23 nm) with perfect PDI values (0.387±0.05–0.835±0.03). The negative values of zeta potential indicated that all prepared formulae were stabilized by electrostatic repulsion forces. Stability studies confirmed that proniosomes give a more stable system that could overcome the problems of standard niosomes. Formulae with the smallest particle size, higher surface charge values and best flow properties were selected to be loaded with poorly soluble drugs for further study. Conclusion: The obtained results offered evidence that spray-dried lactose based proniosomes are promising stable drug delivery carriers and ready to incorporate various poorly water-soluble drugs in order to improve their limited oral bioavailability.